Disparities in depression among Chinese older adults with neurodegenerative diseases. (4th March 2022) - Hao, Zhichao; Ruggiano, Nicole; Li, Qingyi; Guo, Yuqi; Pan, Xiaofu
Abstract: Objectives: Neurodegenerative diseases (NDs), such as Parkinson's disease and Alzheimer's disease and related dementias, are a leading cause of death and disability in China. Although studies have demonstrated that depression is associated with NDs, little is known about the factors impacting this relationship. This study aimed to explore and identify the risk and protective factors of depression among Chinese older adults with NDs. Methods: Data selection was based on the behavioral model of late-life depression. Data from the latest wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS, 1998-2014) in 2014 were analyzed. Among the sample, 334 older adults aged 65 and older with NDs were included in the analysis. A logistic regression analysis was conducted by SPSS 24.0. Results: Participants who lived in urban areas ( O.R. = 2.494, p < .05) or needed more support for Activity of Daily Living ( O.R. = 1.136, p < .05) were more likely to have depression. Participants who lived with household members ( O.R. = .380, p < .05), self-reported their health status as fair ( O.R. = .250, p < .01), or believed their health status remained the same ( O.R. = .331, p < .01) were less likely to have depression. Conclusion: Our findings suggest that policymakers and healthcare professionals should pay specific attention to the regional disparities of healthcare services and the cultural background to understand the relationship between NDs and depression and improve the well-being of ND patients.